Histopathological changes associated with oxidative stress induced by electromagnetic waves in rats’ ovarian and uterine tissues - Ali S. H. Alchalabi; Hasliza Rahim; Erkihun Aklilu Woldegiorgis; Imad Ibrahim Ali Al-Sultan; Abd Rahman Aziz; Mohd Fareq Malek; Suzanna Ronald; Mohd Azam Khan Goriman Khan (2015)
An experimental study was conducted to evaluate the histopathological changes in ovarian and uterine tissues associated with oxidative stress induced by electromagnetic waves. Thirty female Sprague-Dawley of 180 g body weight and three months old were used in this study. The animals were divided into control and experimental groups and were exposed to 1800 MHz GSM radiofrequency radiation emitted by signal generator for 2hrs. /day for 30 and 60 days. Following exposure, serum, ovaries and uterine samples were collected for biochemical and histopathological investigations. Biochemical analysis showed alterations in oxidative stress parameters in both ovaries and uterine tissues from the exposed groups. The histopathological changes were more prominent in experimental groups and vacuolation were observed in the interstitial, granulosa, luteal cells and ooplasm of the ovaries. . Other histopathological changes are disorientation of corona radiata and disruption and thinning of zona pellucida. Cellular nucleus changes similar to fragmentation of nucleus were also seen and this may indicate the start of degeneration process at Graffian follicles as well as micronuclei formation in oocyte nucleus and in some luteal cells. Histopathological changes in uterine tissues were confined to increase in height of luminal epithelium cells, severe apoptosis of glandular and luminal epithelium cells, and severe eosinophils, polymorphoneuclocytes lymphocytes and macrophages infiltration in myometrium and endometrium layers. Vascular congestions were also observed indicating the existence of inflammatory responses in the endometrium. The results from this study suggest that the potential alteration of antioxidant capacity may contribute to the endometrial oxidative damage that could be related to the pathogenesis and progression of endometritis.